PENGEMBANGAN PARIWISATA BERBASIS ALAM OLEH MASYARAKAT DESA GONDORIYO SEMARANG UNTUK PENINGKATAN PEREKONOMIAN WARGA - Tasya Salsabilla (Universitas Ahmad Dahlan, 2020)
The writing of this article is intended to explain the development of tourism by villagers in Gondoriyo to improve the welfare of citizens. The method for updating this article is to read various references in scientific journals that discuss the development of bases to improve citizens' finances, then analyze them and present them systematically in this article. The results of this article discuss the topics, namely: 1) The origins of the development of the Gondoriyo waterfall 2) The role of the community in the development of the Gondoriyo waterfall 3) Obstacles in the development of the Gondoriyo waterfall 4) The benefits of the development of the Gondoriyo waterfall for the development of the Gondoriyo welfare village. Based on the results of a study submitted by the village-based community developer Gondoriyo is very effective to improve the economy of citizens.